A cross-sectional comparison of brain glucose and ketone metabolism in cognitively healthy older adults, mild cognitive impairment and early Alzheimer's disease - Croteau, E.; Castellano, C.A.; Fortier, M.; Bocti, C.; Fulop, T.; Paquet, N.; Cunnane, S.C. (Experimental gerontology, 2018)
Deteriorating brain glucose metabolism precedes the clinical onset of Alzheimer's disease (AD) and appears to contribute to its etiology. Ketone bodies, mainly β-hydroxybutyrate and acetoacetate, are the primary alternative brain fuel to glucose. Some reports suggest that brain ketone metabolism is unchanged in AD but, to our knowledge, no such data are available for MCI. To compare brain energy metabolism (glucose and acetoacetate) and some brain morphological characteristics in cognitively healthy older adult controls (CTL), mild cognitive impairment (MCI) and early AD. 24 CTL, 20 MCI and 19AD of similar age and metabolic phenotype underwent a dual-tracer PET and MRI protocol. The uptake rate constants and cerebral metabolic rate of glucose (KGlu, CMRGlu) and acetoacetate (KAcAc, CMRAcAc) were evaluated with PET using [18F]-fluorodeoxyglucose ([18F]-FDG), a glucose analogue, and [11C]-acetoacetate ([11C]-AcAc), a ketone PET tracer. Regional brain volume and cortical thickness were evaluated by T1-weighted MRI. In AD compared to CTL, CMRGlu was ~11% lower in the frontal, parietal, temporal lobes and in the cingulate gyrus (p<0.05). KGlu was ~15% lower in these same regions and also in subcortical regions. In MCI compared to CTL, ~7% glucose hypometabolism was present in the cingulate gyrus. Neither regional nor whole brain CMRAcAc or KAcAc were significantly different between CTL and MCI or AD. Reduced gray matter volume and cortical thinning were widespread in AD compared to CTL, whereas, in MCI compared to CTL, volumes were reduced only in the temporal cortex and cortical thinning was most apparent in temporal and cingulate regions. This quantitative kinetic PET and MRI imaging protocol for brain glucose and acetoacetate metabolism confirms that the brain undergoes structural atrophy and lower brain energy metabolism in MCI and AD and demonstrates that the deterioration in brain energy metabolism is specific to glucose. These results suggest that a ketogenic intervention to increase energy availability for the brain is warranted in an attempt to delay further cognitive decline by compensating for the brain glucose deficit in MCI and AD. •Brain energy hypometabolism in MCI and AD is specific to glucose.•Mild ketone hypermetabolism occurs in some regions in MCI•Ketogenic interventions may correct the brain glucose deficit in MCI or AD.